Islamic Insurance : A modern approach to Islamic banking - Khorshid, Aly (RoutledgeCurzon, 2004)
The book uses relevant Quranic and Sunnah extracts, and the arguments of pro- and anti-insurance jurists to arrive at its conclusion that Muslims can enjoy the peace of mind and equity of an Islamic insurance scheme.